Escrever com inteligência : contribuições pedagógicas da inteligência artificial para o desenvolvimento de habilidades de produção escrita de alunos do ensino médio - Busetti, Jasmine Cristina (My University, 2025)
This thesis aims to propose strategies for the use of Artificial Intelligence, especially the ChatGPT platform, as a pedagogical resource in the development of high school students' writing skills, using the Text Linguistics. The research is organized into three parts. The first part focuses on the development of concepts of text and textual principles according to authors such as Koch (2009), Halliday and Hasan (1976), Beaugrande and Dressler (1981), and Antunes (2009). It also includes a cognitive approach to writing production, highlighting the models proposed by Flower and Hayes (1981, 1996). Additionally, it presents an analysis of the BNCC (National Common Curricular Base), focusing on the competencies and skills that contribute to the teaching of argumentative-essay writing, justified by the importance of the Enem exam for high school students. The second part presents a critical analysis of the application of AI platforms in education, considering both how these platforms work and their documented uses in educational contexts. Finally, the last chapter presents a proposal for a didactic sequence based on Schneuwly and Dolz (2004), which integrates the use of ChatGPT as an auxiliary tool in students' writing production. The proposal considers the teacher's active mediation and takes place at strategic moments of the lessons, prioritizing the development of students' socio-cultural repertoire, the correction of linguistic deviations, and the construction of writing autonomy. The didactic sequence also encourages critical use of AI, promoting ethical and technical reflections on its application, aligning technical textual aspects, current legislation, and an educational perspective that views technological trends as the future of education. [resumo fornecido pelo autor]
Esta dissertação tem como objetivo geral propor estratégias de utilização da Inteligência Artificial, especialmente a plataforma ChatGPT, como recurso pedagógico no desenvolvimento das habilidades de produção escrita de estudantes do Ensino Médio, à luz da Linguística Textual. A pesquisa está organizada em três partes. Primeiramente desenvolve o conceito de texto e princípios textuais segundo autores como Koch (2009), Halliday e Hasan (1976), Beaugrande e Dressler (1981) e Antunes (2009), além de uma abordagem cognitivista da produção escrita, com destaque para os modelos de Flower e Hayes (1981, 1996), desenvolve também uma leitura da BNCC focalizada nas competências e habilidades que contribuem para o trabalho de produção textual dissertativa-argumentativa, justificada na importância da prova do Enem para o estudante de Ensino Médio. Na segunda parte é analisada criticamente a aplicação das plataformas de IA na educação, levando em consideração o funcionamento das plataformas e utilizações que já apresentam registro. Por fim, o último capítulo desenvolve uma proposta de Sequência Didática fundamentada em Schneuwly e Dolz (2004), que integra o uso do ChatGPT como ferramenta auxiliar na produção textual dos alunos. A proposta considera a mediação ativa do professor e ocorre em momentos estratégicos das aulas, priorizando o desenvolvimento do repertório sociocultural dos estudantes, a correção de desvios linguísticos e a construção de autonomia na escrita. A Sequência Didática estimula ainda o uso crítico da IA, promovendo reflexões éticas e técnicas sobre sua utilização, alindo aspectos textuais técnicos, a legislação em vigência e uma perspectiva educacional que observa as tendências tecnológicas como o futuro da educação. [resumo fornecido pelo autor]
Keywords: Escrita - Estudo e ensino; Inteligência artificial; Educação; Ensino médio; Tecnologia educacional; Writing - Study and teaching; Artificial intelligence; Education; High school; Educational technology